Common Stock Offerings and Earnings Expectations: A Test of the Release of Unfavorable Information. - Brous, Peter Alan (Journal of Finance, 1992)
This paper examines the revisions of analysts' forecasts of future earnings around announcements of common stock offerings. The forecasts of the correct year earnings are, on average, decreased when firms announce plans to issue additional common stock. The size of the decrease is significantly related to announcement period abnormal stock returns. In contrast, forecasts of the five-year growth rate of earnings are, on average, unchanged. The authors interpret these results as being consistent with the claim that equity offering announcements convey unfavorable information regarding the firm's short-term, but not its long-term, earnings prospects.